2015
DOI: 10.1177/2158244015621346
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Size of Public Expenditure in Nigeria

Abstract: Analysis of public expenditure constitutes a central issue in public sector economics and public finance literature. Understanding the reasons for government spending growth has been a central concern of public sector economists. This is due to the fact that most economies of the world have consistently had increased government expenditures. Nigeria is not an exception. There is need to ascertain the determinants of size of government expenditure in Nigeria. Short-Run Error Correction Model and long-run static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 32 publications
5
31
0
4
Order By: Relevance
“…These findings are similar to those of Ukwueze (2015) and Okafor and Eiya (2011). These findings further support the positive theory of public expenditure for Peacock and Wiseman (1961) which states that government expenditure and taxes are positively related due to the displacement effect.…”
Section: Error Correction Modelsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings are similar to those of Ukwueze (2015) and Okafor and Eiya (2011). These findings further support the positive theory of public expenditure for Peacock and Wiseman (1961) which states that government expenditure and taxes are positively related due to the displacement effect.…”
Section: Error Correction Modelsupporting
confidence: 87%
“…Total debts significantly influenced the size of government expenditure only in the short run. Both studies by Ukwueze (2015) and Okafor and Eiya (2011) are in line with the Ricardian equivalence theory implying that both taxes and borrowings constitute essential equivalent forms of financing public expenditures in Nigeria. Kanano (2006) on the other hand also examined the determinants of public expenditure growth in Kenya using the time series data analysis technique for the period 1980 to 2004 through the OLS estimation method.…”
Section: Empirical Literaturesupporting
confidence: 55%
“…Government spending is also positively related with employment, total govenrment debt and government revenue, implying that a percentage change in each of these explanatory variables will lead to a 0.76 percent, 0.05 percent and 0.098 percent in government spending respectively. Specifically, in terms of the positive relationship between government revenue and government spending, findings of this study resonates with the underlying assumptions of Wagner's Law (Wagner, 1893) and findings of Ukwueze (2015), which maintains that as government revenue increases, there is a desire by the government to increase spending to meet the demands of the people, which eventually exacerbates government spending. The positive association between employment and employment can be explained by the fact that in most cases, unemployment paves a way for government job creation which is done through fiscal expansions such as government spending (Boushey & Ettlinger, 2011).…”
Section: Ardl Bounds Tests and Long-run Analysissupporting
confidence: 80%
“…Studies have endeavoured to examine the determinants and drivers of government spending in both developed and developing economies. A study conducted by Ukwueze (2015) in Nigeria, in an attempt to determine the size of the public sector in Nigeria, found that revenue and investment spending have an influence on government spending in the short-run. The study reports that public debt tends to increase government spending and subsequently hinders growth.…”
Section: Empirical Findingsmentioning
confidence: 99%
“…Fiscal functions of government are essential specifically for underdeveloped and developing countries because government expenditure creates a path to boost up their national output (Ukwueze, 2015). Over the years, the structure and size of the public sector regarding its expense have grown tremendously in many economies, especially after the 2 nd World War.…”
Section: Introductionmentioning
confidence: 99%